Desenvolvimento de um dispositivo para monitoramento de painéis fotovoltaicos - Bastos, Matheus Fonseca (2019)
The continuous search for the development of a sustainable energy matrix represents today one of the biggest challenges facing humanity and, among the many actions that can be taken, the use of alternative renewable energy sources is undoubtedly one of the most important. Among the alternative sources of renewable energy, photovoltaic solar energy is receiving the most attention within the current scientific community, as it is a clean, renewable and low maintenance source. However, although it has several benefits, being a relatively new technology compared to traditional sources, it needs some care, as well as frequent monitoring of its operation. In this context, the work aims to design and develop a device, through free hardware, for monitoring and data acquisition of a photovoltaic solar panel. It is also intended to monitor the incidence of solar irradiance on this panel, in order to analyze both the generation and its efficiency, using fuzzy logic concepts. For this, a wemos atmega2560 wifi microcontroller board will be used, which will be responsible for the entire data processing, acquisition and transmission base. In addition, sensors will be used for voltage and current (INA 219), temperature / humidity (BME 280) and infrared (MLX 90614) reading for panel surface temperature. The data will be stored on both the Blynk platform server and a data card (datalogger). Finally, tests were performed in order to validate the quality and reliability of the device in various scenarios, thus concluding that the device presented good stability and reliability in data acquisition and transmission